Perspectives of mutual collaboration of BRICS countries in innovation sphere of enterprise activities - VDOVINA, S.V.; GUSAROVA, L.V.; PUGACHEVA, M.A; PETROVA, E.A. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT The article analyzes the prerequisites and reasons for the unification of BRICS countries. It considers the level of innovative development of the participating countries in the light of international ratings, and conducts a SWOT analysis of the strengths and weaknesses of BRICS countries in innovation. Today there are many works devoted also to the economic development of BRICS countries. In this regard, an important task is the need to study possible "points of contact" in the development and use of the innovative potential of BRICS countries for cooperation in this area. RESUMEN El artículo analiza los requisitos previos y las razones para la unificación de los países BRICS. Considera el nivel de desarrollo innovador de los países participantes a la luz de las calificaciones internacionales, y realiza un análisis FODA de las fortalezas y debilidades de los países BRICS en innovación. Hoy en día hay muchos trabajos dedicados también al desarrollo económico de los países BRICS. En este sentido, una tarea importante es la necesidad de estudiar posibles "puntos de contacto" en el desarrollo y uso del potencial innovador de los países BRICS para la cooperación mutua en esta área.